PENERAPAN WEBSITE E-COMMERCE MADU RIMBA MENGGUNAKAN CMS WORDPRESS DI PT TRAVELING MEDIA NETWORK - Jauharul Maknunah; Dhiya Ulhaq Dazakiyyah; Sujito (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
ABSTRACT The development of technology that has existed to date, all activities can be carried out with the help of the internet, one of which is buying and selling activities that can be done through an e-commerce. There are so many advantages to using e-commerce as a place of buying and selling from the seller's and buyer's side of them, we can sell our products without renting a place to sell, we can buy a product with a fairly long distance without having to go to the place, we also can increase sales by reaching more and wider buyers. Development of an E-commerce website selling honey which was carried out at the office of PT. Traveling Media Network is an effective application of technological developments for buying and selling activities. This website was created with the aim of selling honey through an e-commerce website.This e-commerce website was created using a Content Management System(CMS). The honey sales website is called Madurimba. With the creation of an e-commerce website, Madurimba can be used to facilitate the marketing and sale of honey through a website that can reach a wider and more buyer. On the Madurimba website there are features that can facilitate the buying and selling process, such as calculating shipping costs based on the location we input, so we don't need to calculate it again. Keywords: E-commerce, Content, Management, System , Honey